Estudio de los procesos productivos para mejorar la competitividad en el centro de acopio y producción Jatarishun - Chávez Poveda, Carlos Jonathan (2018)
This research focuses on the study of production processes for the treatment of some Andean grains at the Jatarishun Collection and Production Center, whose primary purpose is optimize the use of space and resources by eliminating unnecessary production times caused by the bad distribution of the machines. Because of the information collected from the conditions of the installation and the characteristics of the machinery was possible to demonstrate the real situation of the production processes in the collection center. The project has layout, man-machine diagrams for each product, process flow and production times that were examined by timing to know which are the real times of each activity included in the treatment of grains such as: corn, chochos, morocho and barley, the research methodology was based on bibliography, participant observation and field research. The proposed activities were achieved through the determination of faults that affect the process, under established methods such as process flow diagram, man-machine diagram and the design of the plant that are the main components for the production lines, so the redistribution of machines in plant is proposed to have a better productivity. Finally, it was recommended the proposals for improvements, it was prepared the Layout of the company with the old and improved model that reflects a better optimization of times and movements, thus increasing the production of the Collection Center for profit of partners and neighboring farmers, obtaining an adequate treatment to maintain the quality of the grains and in this way greater acceptance and confidence among the consumers that contribute to the development of the canton and the province of Cotopaxi.